A new genus and species of Pheronematidae (Porifera: Hexactinellida: Amphidiscosida) from the western Pacific Ocean - Gong, Lin; Li, Xinzheng (Zootaxa, 2017)
A new genus and species of glass sponge, belonging to the family Pheronematidae, is described from a single specimen collected from a seamount near Yap Trench in the western Pacific Ocean. Pheronemoides fungosus gen. et sp. nov. is described based on external morphology. In Pheronemoides gen. nov. the basalia are grouped in a broad semicircular tuft attaching to the dermal surface, and marginalia are located on the boundary between the atrial and dermal surfaces. Given the positions of the basalia and the marginalia, we recognize Pheronemoides as a transitional genus between Pheronema and Sericolophus. We also used a partial sequence of the 16S rDNA gene to confirm the validity of the new species designation.